Adsorption Behaviour of Normal Paraffins in a Fixed Bed Adsorber Containing 5 Å Molecular Sieves - Liu Jichang; Shen Benxian; Sun Hui (Adsorption Science & Technology)
The adsorption process for separating normal paraffins from naphtha using 5 Å molecular sieves was studied with the purpose of optimizing the utilization of naphtha and providing a proper allocation of the feeds for the steam cracking and catalytic reforming processes. The separation efficiency of the normal paraffins was > 99.9% while their purity in the desorption oil could reach 98.2%. The effects of adsorption temperature and space velocity on the adsorption process were investigated. The adsorption capacity was large and the adsorption mass-transfer zone was short when the adsorption temperature was low in the range of 180–340°C and the feed space velocity was small in the range of 30–300 h −1 . The adsorptivity of the normal paraffins improved with increasing carbon number. Long-chain normal paraffins had a notable displacement desorption relative to short-chain normal paraffins.